Meningkatkan Minat Membaca al-Qur’an pada Anak Usia Dini Melalui Metode Qiroati (Studi Kasus di TPQ Nurussalam Lau Dawe Kudus) (PIAUD IAIN Kudus, 2019)
Abstract. The Qur'an is a holy book which is the main source of Muslims. Teaching al quran is a virtue, especially in childhood. Determination of the use of methods in the teaching of the Qur'an is one thing that is very important in facilitating children to be fluent, fast, precise, tartil, and correct in reading the Qur'an. One method in Qur'anic learning is the method of Qiroati. In particular, the problems that the researchers raised in this study were; 1) What is the implementation of the Qiroati method in Nurussalam Lau TPQ, Dawe Kudus? 2) What are the advantages and disadvantages of the Qiroati method in Nurussalam Lau TPQ, Dawe Kudus? 3) What are the factors that support and hinder the implementation of the Qiroati method in Nurussalam Lau TPQ, Dawe Kudus? This research is qualitative research with descriptive-analytical method. The technique of collecting data through observation, interviews and documentation. The results of the study show that 1) the Qiroati method applied in Nurussalam TPQ Lau Dawe Kudus is to practice directly the material that has just been given with teaching aids, by reading or imitating then the deposits individually. 2) The advantages of the Qiroati method in Nurussalam TPQ Lau Dawe Kudus, namely learning focused on santri by direct practice using both teaching aids and individual deposits. While the drawback is the emergence of a lack of enthusiasm. 3) The supporting factors are full support from the institutions, adequate media and sources, restrictions on the number of santri. While the inhibiting factors are environmental factors, namely from parents and the lack of classrooms. Researchers can conclude that the implementation of the qiroati method has been proven to increase children's reading interest in reading the Qur'an in Nurussalam TPQ Lau Dawe Kudus. Keywords: Increase reading interest the Qur'an, Early Childhood, Method Qiroati